School as a Repetition Institution. Asking for Change Possibilities with Michel Foucault and Gilles Deleuze - Archacka, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The aim of the text is to show the conditions and possibilities of introducing a change in the school institution. The writer does it in the context of analyses and comments to the thoughts of the creators of the critical theory ? Theodor Adorno and Max Horkheimer and poststructuralism philosophers? Gilles Deleuz and Michel Foucault. The ?repetition? mentioned in the title constitutes the school nature that reproduces its identity and whose actions undergo the formula of uniforming all elements of the educational process. This procedure, referring to the G. Deleuze?s machine concept, is called by the writer as ?coding the world?. Reflecting on the phenomenon of taking over the discourse concepts of critical pedagogy and putting them down to the practice and action dimensions, he pays attention to the concept of reflectivity, important in the context of the postulate of humanising the Polish school of reflectivity in order to indicate a shape in which it could come to the existence in so-designed education formula.